1992
DOI: 10.1111/j.1151-2916.1992.tb04243.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Protective Layer During the Hydration of Cement

Abstract: The mechanism for the slow rate of reaction between portland cement and water during the early stage is not well understood, but it probably is controlled by either the rate that the reactants diffuse through a barrier that surrounds the unreacted cement grains or by the rate that nuclei of the stable product form and grow or by both rates. New evidence using environmental scanning electron microscopy is presented about the structure of a layer that forms around the particles of cement. Preliminary observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…the breakdown of skin linkage is irreversible. This model is consistent with both the instantaneous formation of a protective layer on cement [15], and the notion of links or junctions between particles [10,13]. …”
Section: A Structural Modelsupporting
confidence: 81%
See 2 more Smart Citations
“…the breakdown of skin linkage is irreversible. This model is consistent with both the instantaneous formation of a protective layer on cement [15], and the notion of links or junctions between particles [10,13]. …”
Section: A Structural Modelsupporting
confidence: 81%
“…A microstructural model for breakdown [14] was followed by experimental confirmation [15] and an eventual model for the yield stress of suspensions, including cement pastes [16].…”
Section: Historical and Practical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…A similar layer which developed within 30 min was also observed in C 3 S by Bergstrom and Jennings (1992). Further research into this topic showed that the layer forming on the surface of the cement grains was thicker and more continuous than that forming on the C 3 S particles (Sujata and Jennings 1992). More recently, Meredith et al (1995) have shown that, in portland cement, an irregular and discontinuous layer appears on the C 3 S particles as early as 1 min after hydration, form-…”
Section: Initial Research Using the Environmental Scanning Electron Msupporting
confidence: 56%
“…rigidity) on the degree of hydration may be related to the precipitation of hydration products, such as CSH at the pseudo-contact points between particles [8,41,42]. Indeed, during cement hydration, calcium and hydroxyl ions dissolve from the anhydrous cement and lead to the formation of a gelatinous, poorly crystalline skin over the particles [43,44]. The precipitated CSH contributes in turning the soft colloidal interactions to a more rigid ones [9,25].…”
Section: Percolation Time and Rigidification Ratementioning
confidence: 96%